Japan : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation highlights that the economy of Japan rebounded strongly in the first quarter of 2002. Global recovery underpinned a large net export contribution, while special transitory factors-including unseasonably warm weather and anomalies in the small single-family spending survey-boosted household spending. Earlier fiscal stimulus measures boosted public demand, but business and residential investment continued to slump. Even with the strong growth in the first quarter of 2002, real GDP is nevertheless expected to decline by about 1\2 percent on an annual-average basis for 2002 as a whole.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet